Performance monitoring in obsessive–compulsive undergraduates: Effects of task difficulty - Riesel, Anja; Richter, Anika; Kaufmann, Christian; Kathmann, Norbert; Endrass, Tanja (Brain and cognition, 2015)
•A RDC task with three difficulty levels was used to assess ERN and CRN.•The high and low OC groups did not differ in ERN and CRN regardless of difficulty.•ERN decreased with increasing difficulty whereas CRN did not vary with difficulty.•More difficult tasks may not elicit overactive performance monitoring in OC subjects. Both obsessive–compulsive disorder and subclinical obsessive–compulsive (OC) symptoms seem to be associated with hyperactive error-related brain activity. The current study examined performance monitoring in subjects with subclinical OC symptoms using a new task with different levels of difficulty. Nineteen subjects with high and 18 subjects with low OC characteristics performed a random dot cinematogram (RDC) task with three levels of difficulty. The high and low OC groups did not differ in error-related negativity (ERN), correct-related negativity (CRN) and performance irrespective of task difficulty. The amplitude of the ERN decreased with increasing difficulty whereas the magnitude of CRN did not vary. ERN and CRN approached in size and topography with increasing difficulty, which suggests that errors and correct responses are processed more similarly. These results add to a growing number of studies that fail to replicate hyperactive performance monitoring in individuals with OC symptoms in task with higher difficulty or requiring learning. Together with these findings our results suggest that the relationship between OC symptoms and performance monitoring may be sensitive to type of task and task characteristics and cannot be observed in a RDC that differs from typically used tasks in difficulty and the amount of response-conflict.